An investigation into the powers of the Auditor-General SA and its ability to strengthen the quality of democracy in South Africa - Dhansay, Asief (College of Accounting, 2020)
The overall objective of the study is to provide commentary on the extent to which the public sector audit process contributes to the strength of democracy in South Africa by enhancing accountability. By studying audit outcomes, the concerns of the Auditor-General of South Africa (AGSA) around lack of accountability due to auditee non-responsiveness was confirmed. The amendments to the Public Audit Act which give the AGSA the power to sanction individuals is therefore considered necessary as a mechanism to change the culture of non-responsiveness amongst auditees and to therefore ensure accountability going forward. A comparative evaluation was conducted for the Ugandan public service where the Ugandan Auditor General has similar powers. This case study points to the necessity of supreme audit institutions in developing countries having enhanced powers to ensure accountability and thus enhance the quality of democracy, although there may be a trade off with the other dimensions of democracy, bringing in to question the overall quality of democracy. The study also outlines areas for future considerations which may impact on the strength of public financial accountability.